2022
DOI: 10.1038/s41371-022-00666-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the onset of hypertension for workers: does including work characteristics improve risk predictive accuracy?

Abstract: Despite extensive evidence of work as a key social determinant of hypertension, risk prediction equations incorporating this information are lacking. Such limitations hinder clinicians' ability to tailor patient care and comprehensively address hypertension risk factors. This study examined whether including work characteristics in hypertension risk equations improves their predictive accuracy. Using occupation ratings from the Occupational Information Network database, we measured job demand, job control, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A previous study found that hypertension is not associated with gender and rises with older age (4,(16)(17). As part of the aging process, the arteries would be getting stiff and contribute to increased blood pressure (18).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that hypertension is not associated with gender and rises with older age (4,(16)(17). As part of the aging process, the arteries would be getting stiff and contribute to increased blood pressure (18).…”
Section: Discussionmentioning
confidence: 99%